GABA induces activity dependent delayed-onset uncoupling of GABA/benzodiazepine site interactions in neocortical neurons - Gravielle, Maria Clara (2005)
Changes in the function of type A γ-aminobutyric acid receptors (GABAARs) are associated with neuronal development and tolerance to the sedative-hypnotic effects of GABAAR positive modulators. Persistent activation of GABAARs by millimolar concentrations of GABA occurs under physiological conditions as GABAergic fast-spiking neurons in neocortex and cerebellum exhibit basal firing rates of 5 to 50 Hz and intermittent rates up to 250 Hz, leaving a substantial fraction of synaptic receptors occupied persistently by GABA. Persistent exposure of neurons to GABA has been shown to cause a down-regulation of receptor number and an uncoupling of GABA/benzodiazepine (BZD) site interactions with a half-life of ∼24 h. Here, we report that a single brief exposure of neocortical neurons in primary culture to GABA for 5-10 min (t1/2 = 3.2 ± 0.2 min) initiates a process that results in uncoupling hours later (t1/2 = 12.1 ± 2.2 h). Initiation of delayed-onset uncoupling is blocked by co-incubation with picrotoxin or α-amanitin but is insensitive to nifedipine, indicating that uncoupling is contingent upon receptor activation and transcription but is not dependent on voltage-gated Ca2+ influx. Delayed-onset uncoupling occurs without a change in receptor number or a change in the proportion of α1 subunit pharmacology, as zolpidem binding affinity is unaltered. Such activity dependent latent modulation of GABAAR function that manifests as delayed-onset uncoupling may be relevant to physiological, pathophysiological, and pharmacological conditions where synaptic receptors are transiently exposed to GABA agonists for several minutes.